(untitled) (Bangladesh Journal of Botany, 2021)
A novel wild strain of Lepista sordida mushroom was collected from a soybean field in Liujiaba at Dazhou district of south western area of China in 2015.The morphological description and molecular identification were conducted to confirm the species. In the present study, optimization was carried out from mycelial growth and fruit body production. For DAAS-E70, the best growth rate was obtained using yeast malt extract, pH 6.0 and temperature 25°C. The wheat grain mushroom spawn was used for upscaling of the mycelium to be used for fruiting body production. In the field experiments, the average biological efficiency of DAAS-E70 was higher than that of Jilin-1, in which, DAAS-E70 accounting for 41.22% of the average biological efficiency, while the Jilin-1 was 35.02%. The stable biological efficiency of DAAS-E70 in different environments and seasons showed that the DAAS-E70 could be used for its commercial cultivation and could provide a new reference for its artificial domestication. Bangladesh J. Bot. 50(3): 813-818, 2021 (September) Special